PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KERJA KARYAWAN PADA PT ADVINDO KIKAKU KOTA TANGERANG SELATAN - Saputri, Annisa; Wiguna, Melda (Journal of Research and Publication Innovation, 2023)
This study aims to determine the effect of work motivation and work discipline on the work performance of employees of PT Advindo Kikaku, South Tangerang. This research is quantitative. The sampling technique used saturated sampling and obtained a sample of 68 respondents. The results showed that: (1) work motivation has a positive effect on employee work performance with the regression equation Y = 18,469 + 0,588X1, the correlation coefficient value is 0,650 meaning that the independent variable and the dependent variable have a strong relationship level, the coefficient of determination is 42,3 % while the remaining 57,7% is influenced by other factors, hypothesis testing obtained t count 6,951 > t table 1,668 and a significant value of 0,000 <0,05 so, Ho1 is rejected and Ha1 is accepted (2) Work discipline has a positive effect on employee work performance with the regression equation Y = 20,790 + 0,530X2, the correlation coefficient value is 0,653 meaning that the independent variable and the dependent variable have a strong relationship level, the coefficient of determination is 42,6 % while the remaining 57,4% is influenced by other factors. hypothesis testing obtained t count 7,002 > t table 1,668 and a significant value of 0,000 <0,05 so, Ho2 is rejected and Ha2 is accepted (3) Work motivation and work discipline have a positive and significant effect on employee work performance with the regression equation Y = 15,522 + 0,343X1 + 0,315X2, the correlation coefficient value is 0,707 meaning that the independent variable and the dependent variable have a strong relationship level, the coefficient of determination is 50 % while the remaining 50% is influenced by other factors, the hypothesis test is assessed by f count of 32,468 > f table of 3,99 and a significant value of 0,000 <0,05 then Ho3 is rejected and Ha3 is accepted, meaning that work motivation and work discipline simultaneously affect employee performance.